2018
DOI: 10.1016/j.redox.2017.09.017
|View full text |Cite|
|
Sign up to set email alerts
|

Complement receptor 3 mediates NADPH oxidase activation and dopaminergic neurodegeneration through a Src-Erk-dependent pathway

Abstract: Microglial NADPH oxidase (Nox2) plays a key role in chronic neuroinflammation and related dopaminergic neurodegeneration in Parkinson's disease (PD). However, the mechanisms behind Nox2 activation remain unclear. Here, we revealed the critical role of complement receptor 3 (CR3), a microglia-specific pattern recognition receptor, in Nox2 activation and subsequent dopaminergic neurodegeneration by using paraquat and maneb-induced PD model. Suppression or genetic deletion of CR3 impeded paraquat and maneb-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 58 publications
3
58
0
Order By: Relevance
“…Furthermore, Yeh et al (2013) found that modulated Src−ERK1/2−NF-κB pathway could attenuate LPS−induced PGE 2 and NO production in BV−2 microglial cells. Besides, Hou et al (2017) demonstrated that Src-Erk-dependent pathway was involved in complement receptor 3-mediated NADPH oxidase activation and dopaminergic neurodegeneration. In addition, our previous study showed that inhibiting Src signaling pathway may have potential anti-neuroinflammatory effects (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Yeh et al (2013) found that modulated Src−ERK1/2−NF-κB pathway could attenuate LPS−induced PGE 2 and NO production in BV−2 microglial cells. Besides, Hou et al (2017) demonstrated that Src-Erk-dependent pathway was involved in complement receptor 3-mediated NADPH oxidase activation and dopaminergic neurodegeneration. In addition, our previous study showed that inhibiting Src signaling pathway may have potential anti-neuroinflammatory effects (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Gait measurement was performed by two individuals blind to the treatment and was analyzed as previously described 52 . The forelimbs and hindlimbs of each mouse were coated with red and blue nontoxic paints, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The cultures were maintained at 37 °C in the incubator with 5 % CO 2 and 95% air in minimum essential medium. The cultures were ready for experiments 7 days later, when the cultures became mature and stable of each cell component (~10% microglia, ~50% astrocytes, ~40% neurons and ~1% dopaminergic neurons) as described previously 52 . Microglia-depleted neuron-glia cultures were obtained by depleting microglia in neuron-glia cultures with 1.5 mM of LME 48 h after seeding (~45 % neurons and ~55 % astrocyte), as described previously 54 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of ERK by phosphorylation is a key step in regulation of microglial pro-inflammatory phenotype [33,34], and is known to play a role in microglial pro-inflammatory processes in a Parkinson's disease mouse model [35,36]. We hypothesized that this pathway might be involved in promotion of the anti-inflammatory phenotype by monomeric α-Syn.…”
Section: Monomeric α-Syn May Regulate Microglia Towards Anti-inflammamentioning
confidence: 99%